2023 IFCN & ILAE minimum recording standards for routine and sleep EEG. Applicability assessment in Russia - E. Yu. Novikova; A. A. Ivanov (Эпилепсия и пароксизмальные состояния, 2024)
In 2023, the International Federation of Clinical Neurophysiology (IFCN) and the International League Against Epilepsy (ILAE) published the most up-to-date recommendations for conducting EEG examinations. The document sets out minimum standards necessary to improve the accuracy, efficiency, and reliability of routine and sleep EEG recordings. At the same time, it is indicated that based on availability specific rules and methods for conducting examinations should be proposed by medical organizations or departments independently. We present a selective translation of such recommendations and an assessment of their compliance with contemporary real-world opportunities in the Russian Federation. The possible “growth points” for the EEG technique in Russia are highlighted as well.